HUBUNGAN TINGKAT PENGETAHUAN TENTANG MENSTRUASI DENGAN TINGKAT KECEMASAN REMAJA AWAL PUTRI DALAM MENGHADAPI MENARCHE DI SD SARASWATI TABANAN - Desak Made Firsia Sastra Putri (STIKES ADVAITA MEDIKA TABANAN, 2023)
Background: Lack of knowledge about menarche is one of the causes of anxiety disorders in young women because not all young women know about menarche or menstruation and how to deal with it. Objective: to determine the relationship between the level of knowledge about menstruation and the anxiety level of young women in facing menarche at SD Saraswati Tabanan Method: Using Correlational Analytic design with cross sectional approach. The sampling technique in this study was purposive sampling with inclusion and exclusion criteria. The subjects in this study were 58 grade V students at SD Saraswati Tabanan Data collection was carried out using a questionnaire sheet. The statistical test used in this study is the Spearman-Rank Test. Results: Most of the respondents had a good level of knowledge with a mild level of anxiety as many as 19 respondents with a percentage of 76.0%, a sufficient level of knowledge with a moderate level of anxiety as many as 17 respondents with a percentage of 70.8%, a lack of knowledge with a moderate level of anxiety as many as 9 respondents with a percentage of 100%. Based on the results of the Spearman-Rank correlation test, it was found that the value of p = 0.000 where p <0.05 which means there is a relationship between the level of knowledge about menstruation and the level of anxiety in facing menarche at Saraswati Tabanan Elementary School Conclusion: the level of knowledge about menstruation is related to the anxiety level of early female adolescents in facing menarche, therefore parents and the environment of early female adolescents are expected to provide good information in order to reduce the anxiety level experienced by early female adolescents